KOMBINASI CAUDAL TRACTION DAN MOBILIZATION WITH MOVEMENT LEBIH BAIK DARIPADA KOMBINASI CAUDAL TRACTION DAN SCAPULAR STABILITY EXERCISE DALAM MENINGKATKAN KEMAMPUAN FUNGSIONAL PADA EXTERNAL SHOULDER IMPINGEMENT SYNDROME - Prima Krishna Dharmawan; Ketut Tirtayasa; Wahyuddin -; Ida Bagus Ngurah; I Nengah Sandi; Sugijanto - (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2018)
Shoulder impingement syndrome (SIS) occurs due to the mechanical traumaric from the rotator cuff tendon located in the antero-inferior part of the acromion and clamping due to the shoulder movement position of flexion and internal shoulder rotation. This study aims to prove the enhancement of functional ability by providing combination of caudal traction and mobilization with movement compared with caudal traction and scapular stability exercise. The design of this study is pre test-post test group design. The number of group I sample of 8 patients was given intervention with caudal traction and mobilization with movement combination 3 times a week for 2 weeks, then in group II 8 patients were given combination of caudal traction and scapular stability exercise also performed 3 times a week for 2 week. Functional capacity improvement tests using Shoulder Pain and Disability Index (SPADI). Data were analyzed using statistical program for social science (SPSS) version 18.0. The results showed: (1) There was improvement of functional ability in group I, mean (%) pre 70.352 ± 5.132, and post 10.466 ± 0.517. The result of t-test related shows p value =< 0.001 (p <0,05). (2) There is improvement of functional ability in group II, mean (%) pre 69.727 ± 2.212, and post 21.961 ± 4.251. The result of t-test related shows p value = <0.001 (p <0.05). (3) There are significant differences in Group I and Group II. The result of pre-pre comparative test with independent t-test show p value = 0,605. And result of post-post comparative test with independent t-test shows p value = <0.001 (p <0.05). It was concluded that the combination of caudal traction and mobilization with movement with caudal traction and scapular stability exercise could improve functional ability in external impingement syndrome. There is a significant difference in functional enhancement between caudal traction and mobilization with movement combinations with a combination of caudal traction and scapular stability exercise.